Fasting glucagon as an independent risk indicator for CAD in patient with type 2 diabetes - Kong, Linlin; Chang, Lina; Nie, Jiamin; Gu, Yian; Wang, Xin; Yan, Siyu; Han, Wantong; Sang, Hequn; Tang, Shaofang; Liu, Ming; He, Qing (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the association between fasting glucagon levels and coronary artery disease (CAD) risk in patients with Type 2 Diabetes Mellitus (T2DM).MethodsThis cross-sectional study enrolled 1,739 hospitalized T2DM patients, categorized into T2DM alone and T2DM with CAD (T2DM&CAD) groups. Fasting glucagon levels and clinical characteristics were collected. Multivariable logistic regression models were used to assess this association, with progressive adjustment for confounders.ResultsIn female patients, fasting glucagon levels were significantly higher in the T2DM&CAD group than in the T2DM alone group (13.33 vs. 11.52 pmol/L, P < 0.01). After full adjustment, each 1-SD increase was associated with a 49.2% higher CAD risk (OR: 1.492; 95% CI: 1.099-2.026; P < 0.05). No significant association was found in male patients.ConclusionElevated fasting glucagon is an independent risk indicator for CAD in women with T2DM, but not in men. These findings highlight the potential value of glucagon monitoring in T2DM management, especially for women, and support exploring glucagon-pathway-targeted therapies to reduce cardiovascular complications.